2013
DOI: 10.1016/j.bmcl.2013.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and bioevaluation of viral 3C and 3C-like protease inhibitors

Abstract: A class of tripeptidyl transition state inhibitors containing a P1 glutamine surrogate, a P2 leucine, and a P3 arylalanines, was found to potently inhibit Norwalk virus replication in enzyme and cell based assays. An array of warheads, including aldehyde, α-ketoamide, bisulfite adduct, and α-hydroxyphosphonate transition state mimic, was also investigated. Tripeptidyls 2 and 6 possess antiviral activities against noroviruses, human rhinovirus, severe acute respiratory syndrome coronavirus, and coronavirus 229E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 17 publications
5
66
0
Order By: Relevance
“…The crystal structure of NV Pro shows that it has a two-domain structure similar to those of other viral 3C-like cysteine proteases, with a catalytic triad composed of His-30, Glu-54, and Cys-139 (23,24). NV Pro cleaves at a Q/G or E/G scissile bond, with a preferred substrate specificity for an FxLQ/GP sequence in the P 4 -P 1 /P 1 =P 2 = position, where x is H, Q, N, or A. Small-molecule inhibitors of NV Pro, either designed based on its substrate specificity or screened from compound libraries, have been reported (16,(19)(20)(21)(22). However, except for those that have been tested against an NV replicon system (19,20,22), many of the NV Pro inhibitors were developed by in vitro protease assays and remain to be evaluated using a cell-based system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of NV Pro shows that it has a two-domain structure similar to those of other viral 3C-like cysteine proteases, with a catalytic triad composed of His-30, Glu-54, and Cys-139 (23,24). NV Pro cleaves at a Q/G or E/G scissile bond, with a preferred substrate specificity for an FxLQ/GP sequence in the P 4 -P 1 /P 1 =P 2 = position, where x is H, Q, N, or A. Small-molecule inhibitors of NV Pro, either designed based on its substrate specificity or screened from compound libraries, have been reported (16,(19)(20)(21)(22). However, except for those that have been tested against an NV replicon system (19,20,22), many of the NV Pro inhibitors were developed by in vitro protease assays and remain to be evaluated using a cell-based system.…”
mentioning
confidence: 99%
“…Two of the NV ORF1-encoded enzymes, Pro and Pol, have been extensively studied and also targeted for antiviral therapeutic development due to their essential roles in viral replication (16)(17)(18)(19)(20)(21)(22). The NV Pro is a 3C-like cysteine protease classified in the chymotrypsin-like serine protease superfamily.…”
mentioning
confidence: 99%
“…Anti-protease inhibitors approved for viral infection treatment are interesting examples in this connection. Recently, these inhibitors are screened for their capability to inhibit Mpro and treat SARS infection using in vivo, in vitro, and in silico experiments (34)(35)(36)(37)(38)(39). The clinical trial of LPV showed a significant decrease in virus titer, reduced rate of death, and improved clinical recovery (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The first class includes a peptide chain with an ending reactive group. This kind of inhibitor fits the catalytic site of the enzyme by making a covalent link with Cys145 via its reactive group and therefore it blocks the substrate entry to the active site (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the same group of investigators has described a class of molecules, generally termed dipeptidyl or tripeptidyl transition state inhibitors, which display potent, broad-spectrum activity in enzymatic and cell culture-based assays against several 3C-like proteases of viruses from the families Picornaviridae, Coronaviridae , and Caliciviridae (including NV), which share conserved features in the protease catalytic site (Kim et al, 2012; Mandadapu et al, 2013; Prior et al, 2013; Takahashi et al, 2013). Mechanistically, these molecules have been shown to be covalently bound to the nucleophilic cysteine residue in the catalytic sites of the proteases of NV and poliovirus in co-crystallography studies (Kim et al, 2012).…”
Section: Current State Of Anti-norovirus Drug Discoverymentioning
confidence: 99%